Pete the Kitty and the groovy playdate [book with audioplayer] - Dean, Kim, 1969-; Dean, James, 1957- (Pete the kitty., 2020)
While Pete the Kitty is at a playdate with Grumpy Toad, his friend refuses to share his toys.